2016
DOI: 10.1371/journal.pone.0150249
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii Infection in Seagull Chicks Is Related to the Consumption of Freshwater Food Resources

Abstract: Understanding the spread of Toxoplasma gondii (T. gondii) in wild birds, particularly in those with opportunistic feeding behavior, is of interest for elucidating the epidemiological involvement of these birds in the maintenance and dissemination of the parasite. Overall, from 2009 to 2011, we collected sera from 525 seagull chicks (Yellow-legged gull (Larus michahellis) and Audouin’s gull (L. audouinii)) from 6 breeding colonies in Spain and tested them using the modified agglutination test (MAT) for the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…For example, sea gull chicks that have been fed food obtained from freshwater habitats are more likely to test positive for Toxoplasma gondii infection (Cabezón et al . ). Other studies have found that birds living in urban environments have comparatively less diverse parasite communities due to their diet (Aponte et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, sea gull chicks that have been fed food obtained from freshwater habitats are more likely to test positive for Toxoplasma gondii infection (Cabezón et al . ). Other studies have found that birds living in urban environments have comparatively less diverse parasite communities due to their diet (Aponte et al .…”
Section: Discussionmentioning
confidence: 97%
“…Such habitat-dependent patterns can also be related to foraging habits and food types available within different environments. For example, sea gull chicks that have been fed food obtained from freshwater habitats are more likely to test positive for Toxoplasma gondii infection (Cabez on et al 2016). Other studies have found that birds living in urban environments have comparatively less diverse parasite communities due to their diet (Aponte et al 2014;Rza z d et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Any predator that consumes these tissue cysts will be infected, form cysts themselves and serve as a reservoir of infection; however, completion of the T. gondii life cycle and oocyst production occur only in felids. Mammals can also be infected in utero by an affected mother, but this vertical transmission route is not expected to occur in birds (Cabezón et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, T . gondii has been used as a model for the study of land-to-sea pathogen contamination [ 14 , 15 , 16 ]. Higher flow of T .…”
Section: Introductionmentioning
confidence: 99%